Kajian Penerapan MoT sebagai Inisiasi CRM pada Penyedia Layanan Akses Broadband: FirstMedia - Teja Endra Eng Tju (Ikatan Ahli Informatika Indonesia, 2019)
The Internet has driven the development of e-commerce. Broadband access service providers are able to provide broad coverage and a variety of types of services at relatively low cost. Similar service providers have created competition. As part of CRM (Customer Relationship Management) a broadband access service provider, FirstMedia places the customer at the center of attention, so a high level of service quality and customer satisfaction needs to be achieved and maintained on an ongoing basis. To find out the factors that affect customer satisfaction is one of the issues in FirstMedia. Else is how to model the relationship between those factors with customer satisfaction. All direct service interactions between the company and the customer will have an impact on customer satisfaction level. It is necessary to identify all activities that occur direct interaction between the company and the customer also get a standard relationship model between these interactions and customer satisfaction. The model is based on theories: MoT (Moment of Truth), SERVQUAL (Service Quality) with RATER (Reliability, Assurance, Tangible, Empathy, Responsiveness, and CRM. There are MoT potential on FirstMedia services occurs: Broadband Access, Registration, Installation, Billing, Contact Center, Support Visit. Service quality indicators are built from the Registration, Installation, Billing, Contact Center, Support Visit service using RATER based on SERVQUAL, as a dimension to measure service quality. Broadband Access is a product which performance is used to measure customer satisfaction, because the product is a service, it also uses RATER from SERVQUAL theory to build indicators of Customer Satisfaction.